REFORMA DEL ARTICULO 74 DE LA CONSTITUCION DE LA REPUBLICA DEL ECUADOR A FIN DE QUE LOS SERVICIOS AMBIENTALES PUEDAN SER REALIZADOS POR PERSONAS JURIDICAS, PUBLICAS Y PRIVADAS - Briceño Ortiz, Rubén Darío (2016)
The Rights of Nature, under Chapter VII of the Constitution of the Republic of Ecuador, Article 74 in the second paragraph states: "... The environmental services will not be subject to appropriation..."; implying that only the Ecuadorian government, and by delegation through its institutions, will be responsible for providing environmental services. However, we found that there are numerous private individuals and legal persons who provide environmental services, especially as even corresponds to own and spend large properties to protected areas. There is the case for example in Loja, the Serbian Forest Dr. Aguirre Villamagua area declared forest area and protective vegetation, located at El Sayo, Santiago jurisdiction of the parish, county and province of Loja, seventy hectares. Similarly alone, to cite an example in the province of Loja, in the canton Loja, there is another private forest, called Area Rumi Wilco, at the request of Mr. Orlando Falco and four owners, forest and protective vegetation declares its properties, located on the site Yamburara, parish Vilcabamba Region and province of Loja, in order to undertake in conservation, scientific research and reforestation with native species in the area in perpetuity, soil whose extension is approximately 40 hectares of land very rugged, eroded and fragile to continue the erosion process, because they are unprotected cropland and vegetation for some time; the need to preserve with permanent vegetation, allowing the forest is formed by succession and other suitable methods, such as enrichment with native species to accelerate the process. The Constitution of the Republic of Ecuador, is contradicted by the abovementioned Article 74, to ensure to persons, Article 66: "...26. The right to property in all its forms, function and social and environmental responsibility. The right of access to the property will be effective with the adoption of public policies, among other measures. . 27. The right to live in a healthy, ecologically balanced, free from contamination and in harmony with nature "Similarly, Article 71 states:" ... The State will encourage natural and legal persons and groups, to protect nature, and promote respect for all the elements that make up an ecosystem"Also the types of property that are recognized in Article 321 which states:."The State recognizes and guarantees the right to property in its public forms, private, community, state, associative, cooperative, mixed, and should fulfill their social and environmental role. " Another contradiction of Article 74 of the Constitution is generated with the Environmental Management Act, the law governing all environmental standards; although published in 1999, whose status is in effect, very good structure, given its international contribution and specialists, for example, Article 9 states that corresponds to the Ministry of Environment: "... f) Establish strategies and administrative coordination cooperation with various public and private bodies;...". With regard to social participation mechanisms established in Article 28 that "Every natural or legal person is entitled to participate in environmental management through the mechanisms established for that purpose Regulation, including consultations included , public hearings, initiatives, proposals or any association between the public and private sectors. " And even in the glossary of definitions states: "Protegidas.- Natural Areas are areas of public or private property, ecological, social, historical, cultural and scenic significance, established in the country according to law, order to prevent its destruction and ensure the study and conservation of species of plants and animals, natural landscapes and ecosystems. Environment.- protection is the set of policies, plans, programs, policies and actions to prevent and control environmental degradation. It includes three aspects: environmental conservation, prevention and control of environmental pollution and sustainable management of natural resources. Environmental protection is the joint task of the state, the community, non-governmental organizations and the private sector. " Records which instituted the need to reform the Constitution, including the private sector in the mechanisms of environmental services, which not only can or should make the Ecuadorian State, but also correspond to the private sector; and I stress the numerous examples that I cite, and should even be greater private participation of natural or legal persons, as the state does not have the staff or resources to cover with this, that even meets a huge campaign and commitment and work nationwide education and outreach.